1984
DOI: 10.2170/jjphysiol.34.655
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of regulation of amylase release by .ALPHA.- and .BETA.-adrenergic agonists in rat parotid tissue.

Abstract: The effect of forskolin and isobutyl-methylxanthine on amylase release and cyclic AMP accumulation by a-and f-adrenergic agonists was studied in rat parotid slices. A small increase in cyclic AMP by ~3-adrenergic agonists was sufficient for maximum stimulation of amylase release (YOSHIMURA et al., 1982a), but a similar increase in cyclic AMP by forskolin did not stimulate the maximum amount of amylase release. The amount of amylase release and cyclic AMP changed in parallel when lower doses of isobutyl-methylx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Forskolin also acts to augment hormone-stimulated cyclic AMP production in many tissues (SERMON and DALY, 1981;SERMON et al, 1981). In the parotid gland, our report stipulates that forskolin increases the level of cyclic AMP and potentiates the effect of isoproterenol on tissue cyclic AMP accumulation (YosHIMURA et al, 1984b). The effect of forskolin on cellular cyclic AMP accumulation, however, was not potentiated by either A23187 or oxotremorine, although its effect was augmented by isobutylmethylxanthine.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Forskolin also acts to augment hormone-stimulated cyclic AMP production in many tissues (SERMON and DALY, 1981;SERMON et al, 1981). In the parotid gland, our report stipulates that forskolin increases the level of cyclic AMP and potentiates the effect of isoproterenol on tissue cyclic AMP accumulation (YosHIMURA et al, 1984b). The effect of forskolin on cellular cyclic AMP accumulation, however, was not potentiated by either A23187 or oxotremorine, although its effect was augmented by isobutylmethylxanthine.…”
Section: Discussionmentioning
confidence: 68%
“…Male Wistar rats (200-450 g), normally fed, were killed by cervical dislocation, and the parotid gland was rapidly excised, trimmed of fat and connective tissues and sliced by hand with a razor blade. About 0.5 mm thick slices were put into a flask containing 1 ml of modified Krebs Henseleit phosphate buffer, pH 7.4, 1.03 mM CaC12, 1 mg/ml bovine albumin and 10 mM glucose, as described previously (YOSHIMURA et a!., 1984b), with pure oxygen used as the gas phase. After being weighed (about 20 mg per flask), the slices were preincubated for 10 min by shaking at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…These results suggest that the mechanisms by which isoproterenol and CCh regulate amylase secretion are different. Several studies have shown a potentiation of amylase secretion induced by combined stimulation with cAMPand Ca 2+ -mediated agonists [8,15,16,17,19,20]. However, the role of these two messengers in the mechanism of potentiation has not yet been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Another mechanism to stimulate amylase secretion is activated by Ca 2+ ‐mobilizing agonists such as muscarinic cholinergic, α‐adrenergic and substance P receptor stimulants. Since the removal of extracellular Ca 2+ causes a large reduction in amylase secretion induced by these agonists (Putney et al 1977; Watson et al 1979; Yoshimura et al 1984), changes in [Ca 2+ ] i have been assumed to be crucial to the effects of these agonists. However, the precise role of [Ca 2+ ] i in the regulation of amylase secretion has still not been fully elucidated.…”
mentioning
confidence: 99%